Investigating CENPW as a Novel Biomarker Correlated With the Development and Poor Prognosis of Breast Carcinoma - Wang, Luyang; Wang, Hairui; Yang, Chen; Wu, Yunyi; Lei, Guojie; Yu, Yanhua; Gao, Yan; Du, Jing; Tong, Xiangmin; Zhou, Feifei; Li, Yanchun; Wang, Ying (Frontiers in Genetics, 2022)
Breast invasive carcinoma (BRCA) is a carcinoma with a fairly high incidence, and the therapeutic schedules are generally surgery and chemotherapy. However, chemotherapeutic drugs tend to produce serious toxic side effects, which lead to the cessation of treatment. Therefore, it is imperative to develop treatment strategies that are more effective and have fewer side effects at the genetic level. Centromeric protein W (CENPW) is an oncogene that plays an important part in nucleosome assembly. To date, no studies have reported the prognostic significance of CENPW in breast carcinoma. In this study, we verified that CENPW expression is up-regulated in breast carcinoma and positively associated with the level of immune cell infiltration. The clinicopathological characteristics further suggest that CENPW expression is correlated with a worse prognosis of breast carcinoma. Interestingly, the CENPW mutation contributes to the poor prognosis. Next, we discovered that the genes interacting with CENPW are mainly concentrated in the cell cycle pathway, and CENPW is co-expressed with CDCA7, which is also highly expressed in breast carcinoma and leads to a worse prognosis. Our subsequent studies verified that knockdown of CENPW significantly inhibits the proliferation and migration of breast carcinoma cells and promotes their apoptosis rate. Notably, inhibition of CEMPW sensitizes breast cancer cells to chemotherapeutic drugs that have been found to induce cell cycle arrest. In summary, these results provide extensive data and experimental evidence that CENPW can serve as a novel predictor of breast cancer and may act as a prospective therapeutic target.